Structural investigation of magnetic FeRh epitaxial films. (19th August 2015) - Castiella, M; Gatel, C; Bobo, J F; Ratel-Ramond, N; Tan, R; Respaud, M; Casanove, M J
Abstract: We report on the structural investigation of FeRh thin films exhibiting a magnetic transition from an antiferromagnetic (AF) to a ferromagnetic (FM) state when heated above ≈350 K. The transition lying in a very narrow range of composition, close to the equiatomic one, and in a given chemically ordered phase (of B2-type), the composition and the growth conditions were carefully adjusted in the epitaxial growth process of the films on (001)MgO. Magnetic measurements confirmed the presence of the AF–FM transition. High-angle x-ray diffraction and electron microscopy experiments were used to characterize the FeRh structural details at different scales from statistical to highly localized information. Special attention was paid to the quality of the chemical order and the presence of defects, which condition the characteristics of the magnetic transition. Interestingly, the results reveal the presence of nanograins, displaying another structure in the equiatomic FeRh films, such grains having previously been observed in strained bulk specimens.